The gamification in the design of computational applications to support the autism treatments: an advance in the state of the art - Constain, Gustavo Eduardo (2019)
This paper presents the results found when consulting literature, with the purpose of elaborating the state of the art related to the use of gamification techniques in the development of computational applications that support the treatment of the Autism Spectrum Disorder (ASD). The research focuses on the results of using some models for the design of inclusive software, the steps to elaborate them and the possibility of adapting game techniques; so that its use can be modeled and adapted in a future framework for the design of specific applications for the autism management. Due to its characteristic, the game involves an intrinsic motivation, and a number of sensations that facilitate the development of emotions in the people who interact, that is why the study carried out seeks to find the importance of linking these techniques to the interior of the treatments of ASD, especially when it is intended to develop skills, such as self-recognition and social performance in children suffering from autism. With this article, we also want to propose an initial design framework for inclusive computational applications, based on gamification, related to the achievement of emotional skills in children with ASD.